2019
DOI: 10.1128/jvi.00196-19
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Precore Protein p22 Inhibits Alpha Interferon Signaling by Blocking STAT Nuclear Translocation

Abstract: Antagonism of host immune defenses against hepatitis B virus (HBV) infection by the viral proteins is speculated to cause HBV persistence and the development of chronic hepatitis. The circulating hepatitis B e antigen (HBeAg, p17) is known to manipulate host immune responses to assist in the establishment of persistent viral infection, and HBeAg-positive (HBeAg+) patients respond less effectively to IFN-α therapy than do HBeAg-negative (HBeAg−) patients in clinical practice. However, the function(s) of the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 89 publications
2
47
0
Order By: Relevance
“…HBV wild-type infectious particles were collected from the supernatant of induced HepAD38 cells, HBV RNA particles were collected from the 3TC- or L-FMAU-treated HepAD38 cells upon induction, HBV naked capsids were collected from the supernatant of untreated and 3TC-treated HepDES19 cells upon induction. The infection of HepG2-NTCP12 cells, intracellular HBc immunofluorescence microscopy and HBeAg ELISA were conducted as previously published [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…HBV wild-type infectious particles were collected from the supernatant of induced HepAD38 cells, HBV RNA particles were collected from the 3TC- or L-FMAU-treated HepAD38 cells upon induction, HBV naked capsids were collected from the supernatant of untreated and 3TC-treated HepDES19 cells upon induction. The infection of HepG2-NTCP12 cells, intracellular HBc immunofluorescence microscopy and HBeAg ELISA were conducted as previously published [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…P22 is further truncated, losing the arginine-rich C-terminal domain, to yield HBe (p17), which is secreted [ 19 ]. Expression of p22 was confirmed by immunoblot on whole cell lysates prepared from transfected Huh7 cells using an anti-HBc antibody and, as shown by others [ 19 ], neither p17 nor p25 were detected by immunoblot ( Figure 1 b and Figure S2 ). HBV p17 and p25 were detected by confocal immunofluorescence in transfected Huh7 cells ( Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…During natural HBV infection, p22 is processed to p17 or HBV e antigen (HBeAg) and secreted into the extracellular space [ 19 ]. We confirmed that the transfected p22 is processed to p17 by detecting and quantifying HBeAg in the supernatant of transfected Huh7 cells ( Figure S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that in the setting of high levels of plasmid, even a less-optimal binding alternative may still favour production despite potential structural controls. Therefore, this model may not be representative of natural processes despite successes with this approach for other pathway studies (73)(74)(75). (2) It is also possible that the quadruplex structure is not needed for binding and that the primary nucleotide sequence is the sole influencer of the subtle finding in this model.…”
Section: Discussionmentioning
confidence: 99%